Teknik Penanganan Cepat dan Higienis Hasil Tangkapan di Atas Dek Kapal di SMKN 1 Jeunib - Fuji Sintia Armi; Rizka Maula; Nida Khafiyya; Fanny Indah Sari Berutu; Lia Handayani; Rulita Maulidya (Yayasan Sagita Akademia Maju, 2026)
Improper handling of the catch can accelerate the deterioration of fish quality, reduce market value, and increase the risk of microbiological contamination. Therefore, implementing Good Fish Handling Practices (CPIB) is crucial for maintaining the quality and safety of fishery products from the post-harvest stage onward. This community service activity aims to improve students' and the coastal community's knowledge and skills in techniques for the rapid and hygienic handling of catch on the ship’s deck. The methods used include outreach sessions, demonstrations, and hands-on practice applying the ABCD principles (Careful, clean, quick, and cold). Evaluation was conducted by assessing participants’ understanding before and after the activity and by observing their practical skills. The results showed an improvement in participants’ understanding and skills in applying fish handling techniques in accordance with the CPIB principles. This activity is expected to support efforts to control the quality of fishery products, reduce damage and loss of catch, increase the economic value of fish, and produce competent human resources in the field of fisheries.